Evidence-based Medical Leadership Development: A Systematic Review - Lyon, Oscar (Journal of the Nuffield Department of Surgical Sciences, 2021)
1Alexander Mafi, 2Oscar Lyons, 3Robynne George, 4Joao Galante, 5Thomas Fordwoh, 6Jan Frich, 7Jaason Geerts 1University of Oxford, UK, 2University of Oxford, UK, 3Royal United Hospital Bath NHS Trust, 4Oxford University Hospitals NHS Trust, UK, 5University of Oxford, UK, 6University of Oslo, Norway, 7Canadian College of Health Leaders, Ottawa, Canada Health systems invest significant resources in leadership development for physicians and other health professionals. Competent leadership is considered vital for maintaining and improving quality and patient safety. We carried out this systematic review to synthesise new empirical evidence regarding medical leadership development programme factors which are associated with outcomes at the clinical and organisational levels. 117 studies were included in this systematic review. 28 studies met criteria for higher reliability studies. The median critical appraisal score according to the Medical Education Research Study Quality Instrument for quantitative studies was 8.5/18 and the median critical appraisal score according to the Jonna Briggs Institute checklist for qualitative studies was 3/10. There were recurring causes of low study quality scores related to study design, data analysis and reporting. There was considerable heterogeneity in intervention design and evaluation design. Programmes with internal or mixed faculty were significantly more likely to report organisational outcomes than programmes with external faculty only (p=0.049). Project work and mentoring increased the likelihood of organisational outcomes. No leadership development content area was particularly associated with organisational outcomes. In leadership development programmes in healthcare, external faculty should be used to supplement in-house faculty and not be a replacement for in-house expertise. To facilitate organisational outcomes, interventions should include project work and mentoring. Educational methods appear to be more important for organisational outcomes than specific curriculum content. Improving evaluation design will allow educators and evaluators to more effectively understand factors which are reliably associated with organisational outcomes of leadership development.